PENGETAHUAN MENGENAI GARAM BERIODIUM PADA IBU RUMAH TANGGA DI WILAYAH KERJA PUSKESMAS TAMPAKSIRING I - Wulandari, Kadek Nuansa Putri; Sutiari, Ni Ketut (ARCHIVE OF COMMUNITY HEALTH, 2022)
ABSTRACT Universal Salt Iozation is a strategy to reduce iodine deficiency by adding iodine to salt. In the evaluation of nutritional performance in 2020, Bali is included in a province that is still low on iodized salt consumption, which is 80.6% of the 82% target. The level of public knowledge about iodized salt will influence the scope of use of iodized salt. The purpose of this study was to determine the knowledge of housewives regarding iodized salt in the work area of the Tampaksiring I Public Health Center. This type of research was quantitative descriptive with a cross-sectional approach. The research population is housewives who are in the working area of the Tampaksiring I Public Health Center with a sample of 111. Accidental sampling does sampling. Data collection techniques using interviews and observation. The research instrument used a questionnaire and a checklist. Conducted in April - June 2021 and analyzed using Univariate Analysis. The results of this study obtained that the majority graduated from junior high school (25.2%) and 75.7% as housewives (IRT). 55.9% of respondents have used iodized salt and 59.5% of respondents have good knowledge of iodized salt. Keywords: Knowledge, Iodized Salt, Housewife